An extension of Aaker’s brand personality model from Islamic perspective: a conceptual study - Ahmed, Muhammad; Jan, Muhammad Tahir (Emerald Publishing Group, 2015)
Purpose – The purpose of this paper is to browse literature based on Aaker’s brand personality modal and highlight criticism on it. Furthermore, the study proposes an Islamic brand personality modal based on Islamic teachings.